In vitro toxicity of combination of Amitraz and Carvacrol on Demodex canis - Sina Fereydooni; Farnoosh Arfaee; Mohammad Reza Youssefi; Fatemeh Zahra Gharib; Mohaddeseh Abouhosseini Tabari (Open Veterinary Journal, 2023)
Background: Canine generalized demodicosis is an inflammatory skin disease, which usually has time-consuming and frustrating treatments. Aim: The present study aimed to evaluate the acaricidal activity of carvacrol as a green drug and a combination of carvacrol and amitraz on Demodex canis mites and investigate mite's survival lifetime. Methods: Mite samples were collected from a dog affected by demodicosis and had been diagnosed with deep skin scrapings. The motility of mites was examined by using optical microscopy. Samples were tested with Carvacrol 5%, the combination of Carvacrol 5% + Amitraz 0.05%, Amitraz 0.05% as a positive control, and mineral oil as a negative control. The interval time between the adding the test solutions and the moment the last mite ceased was defined as the survival time in the samples and the killing times of mites in each group were compared with each other. Results: It was determined that after administration of a 5% concentration of Carvacrol, lethal effects were faster than the combination solution of Carvacrol 5% + Amitraz 0.05%, and the survival times in the control groups were longer than in both treatment groups. Conclusion: Carvacrol as one of the most important bioactive terpenes, had the most effective in vitro miticidal activity and it seems that Carvacrol alone or in combination with Amitraz can be suggested as a possible therapy in the treatment of canine demodicosis. [Open Vet J 2023; 13(7.000): 894-902]